What is Stang’s law? - Kortlandt, Frederik (Baltistica, 2017)
Stang’s law is an ambiguous concept. On the one hand, it refers to a retraction of the stress from non-acute long vowels to the preceding syllable in Slavic. On the other hand, it refers to the development of acc.sg. Vedic dyā́m ‘sky’, gā́m ‘bull, cow’, Greek Ζῆν(α), βῶν, from *dieum, *gwoum. Stang derived the long vowel from the diphthong before the tautosyllabic nasal consonant. Alternatively, the long vowel can be attributed to monosyllabic lengthening followed by the loss of *‑u‑ before the tautosyllabic nasal. I have proposed that *‑u‑ was lost before word-final *‑m at a stage before the monosyllabic lengthening, yielding *diēm < *diem < *dieum and *gwēH3m < *gweH3m < *gweH3um. Latvian gùovs reflects the acc.sg. form *gwēH3m with loss of the laryngeal after the long vowel. The paradigm with a full grade suffix *‑eH2‑ and the loss of laryngeals before final *‑m were dialectal Indo-European innovations. Nasal vowels in final syllables lost their nasality in East Baltic. The loss of *‑u‑ before *‑m in Vedic gā́m and Greek βῶν, the rise of the long vowel in these forms, the loss of the laryngeal in Latvian gùovs, the generalization of the full grade *‑eH2‑ in the paradigm, the loss of laryngeals before *‑m, and the loss of nasality in East Baltic final syllables are all chronologically distinct developments, none of which can appropriately be called Stang’s law. It is therefore preferable to use this term only in reference to the retraction of the stress from non-acute long vowels in Slavic, which is the basis of modern Slavic accentology.